Ecology and Evolution of Gall-Inducing Arthropods: The Pattern From the Terrestrial Fossil Record - Labandeira, Conrad C. (Frontiers in Ecology and Evolution, 2021)
Insect and mite galls on land plants have a fair fossil record of damage types (DTs), ichnotaxa and informally described gall morphotypes. The earliest gall is on a liverwort of the Middle Devonian Period at 385 million years ago (Ma). A 70 million-year-long absence of documented gall activity ensues. Gall activity resumes during the Pennsylvanian Period (315 Ma) on vegetative and reproductive axial organs of horsetails, ferns and probably conifers, followed by diversification of early hemipteroid lineages on seed-plant foliage during the Permian Period. The end-Permian (P-Tr) evolutionary and ecological crisis extinguished most gall lineages; survivors diversified whose herbivore component communities surpassed pre-P-Tr levels within 10 million years in the mid Triassic (242 Ma). During the late Triassic and Jurassic Period new groups of galling insects colonized Ginkgoales, Bennettitales, Pinales, Gnetales and other gymnosperms but data are sparse. Diversifying mid Cretaceous (125–90 Ma) angiosperms hosted a major expansion of 25 gall DTs organized as herbivore component communities, each present on early lineages of Austrobaileyales, Laurales, Chloranthales and Eurosidae in the Dakota Fm (103 Ma). Gall diversification continued into the Ora Fm (92 Ma) of Israel with another 25 gall morphotypes, but on a different spectrum of plant hosts, revealing the earliest occurrence of parasitoid attack. The End-Cretaceous (K-Pg) extinction event (66 Ma) almost extinguished host-specialist DTs; surviving gall lineages expanded to pre-K-Pg level 10 million years later at the Paleocene-Eocene Thermal Maximum (PETM) (56 Ma), during a dramatic increase of land surface temperatures and elevated atmospheric pCO2 levels that significantly increased herbivory levels, although gall diversity increased only after the PETM excursion and during the Early Eocene Climatic Optimum (EECO). After the EECO, modern (or structurally convergent) gall morphotypes originate in the mid-Paleogene (49–40) on hosts different than their modern analogs. During subsequent global aridification of the early Neogene ( 20 Ma) the Czech Republic records several modern associations with gallers and plant hosts congeneric with modern analogs. Except for 21 gall DTs from New Zealand, the gall record decreases in richness; an early Pleistocene (3 Ma) study documents a plant species surviving in northern Iran with decreasing host specificity.